Schnebel, Nono, Schönberg, oder, Die wirkliche und die erdachte Musik: Essays und Autobiographisches - Henius, Carla (Hamburg Europäische Verlagsanstalt, 1993)
These texts, reports on the experiences and critical reflections of a singer, teacher and music theatre director, reflect in an illuminating and exciting way not only the problems associated with the performance practice of new music, but also provide a lively insight into the day-to-day worklife of the artists and are at the same time an impressive group portrait of New Music: from composers Theodor Adorno, Fortner, Rihm, Nono, Schnebel and Manzoni to conductors Abbado, Maderna and Zender. (Translated with Deepl.com)
Keywords: Schnebel, Dieter -- 1930-2018; Nono, Luigi -- 1924-1990; Schoenberg, Arnold -- 1874-1951; 20th Century (1901-2000); Music history; Composer; Biography